Study on soil erosion properties and rate at Sungai Jemberau, Tasik Chini - Muhammad Firdaus, Muhammad Asri (2017)
A study on soil erosion properties and rate at Sungai Jemberau, Tasik Chini. In order to determine the rate of erosion on three type of land surface and their soil properties, several related were soil testing conducted in the Geotechnical Laboratory, UMP. Testing that involved are a particle size distribution and moisture content that were carried out in classify properties of the soil sample. The soil trap area is well graded sand with Cu > 4. The riverside and in the river area also is well graded sand with Cu > 4. The moisture content for riverside and in the river surface are 17.52 and 27.43 respectively. The Revised Universal Soil Loss Equation (RUSLE) to predict the average annual soil loss rate at Sungai Jemberau, Tasik Chini. The result indicates that the average annual soil loss (A) for soil loss measured from soil trap to 7 days start from 23 december 2017 to 29 december 2017 is 9.26 x 10-6 g/m2/day.